Short sellers and insider trading profitability: A natural experiment - CHEN, Xia (Institutional Knowledge at Singapore Management University, 2022)
We examine the impact of short sellers on insider trading profitability using a natural experiment of a pilot program which relaxed short-selling constraints for randomly selected pilot stocks. We find that pilot firms experienced a significant decrease in insider trading profitability during the pilot program. The results are more pronounced for the pilot firms with poor information quality, and for the pilot firms without corporate restrictions on insider trading. Our evidence suggests that short sellers serve an important market disciplinary role by reducing insider trading profitability.